The potential benefits of aspirin for primary cardiovascular prevention in rheumatoid arthritis: a secondary analysis of the PRECISION Trial. (20th April 2018) - Solomon, Daniel H; Libby, Peter; Yeomans, Neville D; Wang, Qiuqing; Wolski, Kathy E; Nissen, Steven E; Husni, M Elaine
Abstract: Objective: Guidelines exist for the use of low-dose aspirin in the general population for primary cardiovascular (CV) prevention, but the risk-benefit considerations may differ in RA. While RA confers an increased CV risk, such patients more likely use NSAIDs and corticosteroids. Methods: We conducted a cohort study to assess potential risks and benefits of low-dose aspirin. We estimated incidence rates and hazard ratios (HRs) using Cox regression among subjects with RA but no known CV disease in the Prospective Randomized Evaluation of Celecoxib Integrated Safety Vs Ibuprofen Or Naproxen trial. The primary exposure of interest was low-dose aspirin, and all enrolled patients were provided open-label esomeprazole. The primary composite outcome was major NSAID toxicity, including major adverse CV event (MACE), clinically significant gastrointestinal events, renal events and all-cause mortality. Results: We found 1852 subjects with RA in Prospective Randomized Evaluation of Celecoxib Integrated Safety Vs Ibuprofen Or Naproxen without known CV disease; 540 reported using low-dose aspirin for CV prevention and 1312 did not. Any major NSAID toxicity was observed in 79 (6.0%) non-aspirin users and 37 (6.9%) aspirin users ( P = 0.50). Aspirin users experienced all components of the primary outcome at a similar rate to non-users. In fully adjusted models, the risk for major NSAID toxicity was similar between aspirin exposure groups (HR = 1.08, 95% CI: 0.69, 1.69). The risk for MACE was also similar between exposure groups in age- and gender-adjusted models (HR = 1.23, 95% CI: 0.72, 2.10). Conclusion: RA patients using low-dose aspirin with chronic NSAIDs and esomeprazole had a similar risk of major NSAID toxicity and MACE as patients who did not.